ANALISIS PREDIKSI KEBANGKRUTAN PADA PERUSAHAAN PERTAMBANGAN BATUBARADI BURSA EFEK INDONESIA PERIODE 2013-2015 - Sri Marliawati; Ghazali Syamni; Edi Zulfiar (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2016)
The purpose of this study is to predict the possibility of bankruptcy using Altman Z-Score Model in Coal Mining Companies listed in Indonesian Stock Exchange. This study uses analytical models Altman Z-Score to see how big the coal mining company bankruptcy prediction period 2013-2015. Calculating the each company's bankruptcy prediction on each totaling 19 companies. The data used in this study was obtained annual financial statements of coal mining companies listed on the Indonesia Stock Exchange. The analysis technique used is the bankruptcy Altman Z-score of four variables representing liquidity ratio (X1), profitability ratio (X2), profitability ratio (X3) and solvency ratio (X4). Produces the formula Z-Score = 6.56 X1 + 3.26 X2 + 6.72X3 + 1.05X4. within the Z-Score assessment criteria > 2.60 is categorized as a very healthy company. 1.10 < Zscore < 2.60 are in gray areas so that the chances were saved and the possibility of bankruptcy as much depends on the company's management policy decisions as decision makers and Z-score < 1.10 is categorized category of financial distress and are at high risk so that the possibility of bankruptcy is very large. The study finds that there is the financial condition in coal mining companies during the observation year. Bumi Resources Tbk is the company that has the largest possibility of bankruptcy than others. This study also finds that the Altman Z-Score can be used to predict the possibility of bankruptcy.